Safety and efficacy of omaveloxolone v/s placebo for the treatment of Friedreich's ataxia in patients aged more than 16 years: a systematic review - Ankita Umrao; Monika Pahuja; Nabendu Sekhar Chatterjee (Orphanet Journal of Rare Diseases)
Abstract Background Friedreich’s ataxia (FA) is a rare genetic disorder caused by silencing of the frataxin gene (FXN), which leads to multiorgan damage. Nrf2 is a regulator of FXN, which is a modulator of oxidative stress in animals and humans. Omaveloxolone (Omav) is an Nrf2 activator and has been reported to have antioxidative potential in various disease conditions. The present review was conducted to determine the use of Omav, the only FDA-approved treatment for FA. Methods Three electronic databases, Cochrane, PubMed and Google Scholar, were searched with terms such as ‘Omaveloxolone’, ‘Friedreich ataxia’, ‘genetic diseases’, ‘autosomal recessive’, and ‘rare disorders’ using various advanced search filters. Articles were screened, extracted, and assessed for quality, and a qualitative synthesis of the data was performed. The study protocol was registered in PROSPERO (CRD42024531449). Results A total of 201 records were found, with very few published research articles on the topic. Only two randomized clinical trials published in a series of three research articles were included in the current systematic review. Peak load exercise and modified Friedreich’s Ataxia Rating Scale (mFARS) values were considered the major outcome measures for determining the efficacy of 150 mg Omav capsules/day in FA. Exploratory outcome measures, such as low-contrast letter visual acuity test, exercise test, T25-FW, 9-HPT, health-related quality of life, and biochemical tests, were also assessed along with adverse events in all the studies. Conclusion Although, the quality of the articles demonstrated low bias. However, the short duration, small sample size, and missing data, including the values of different measures of mFARS scores in patients, limit the generalizability of the results. Further studies with longer durations and in severe patients with foot deformities are needed to clearly define the efficacy of Omav in FA and to determine the optimal drug for FA patients in India.